A critique of anti-racism in rhetoric and composition the semblance of empowerment - Smith, Erec (Lexington Books, 2020)
A Critique of Anti-racism in Rhetoric and Composition: The Semblance of Empowerment critiques current antiracist ideology in rhetoric and composition, arguing that it inadvertently promotes a deficit-model of empowerment for both students and scholars. Erec Smith claims that empowerment theory--which promotes individual, communal, and strategic efficacy--is missing from most antiracist initiatives, which instead often abide by what Smith refers to as a "primacy of identity": an over-reliance on identity, particularly a victimized identity, to establish ethos. Scholars of rhetoric, composition, communication, and critical race theory will find this book particularly useful.